Till Labor Cost Do Us Part. On the Long Run Convergence of EMU Countries - Francesca Pancotto; Filippo Maria Pericoli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
A sustainable long-run pattern in the relative competitiveness of euro area countries is a key factor for the survivorship of the monetary union. We analyze the issue focussing on unit labor cost dynamics using cointegration analysis for the whole economy and for the manufacturing sector separately. Our findings show that the introduction of the euro has increased, rather than decreased, the distance among member countries, as measured in the metric of unit labor costs. Dispersion of productivity rather than wage compensation suggests that persisting idiosyncratic dynamics are driven by real factors, i.e. diverging technological patterns rather than by monetary factors, expressed by wage compensation.
Keywords: E31; O47; C32; 330